UTILIZING CORN AS A TEMPE INGREDIENT: DIVERSIFICATION INTO TAPIOCA TEMPE CHIPS - Nurhasanah Nurhasanah; Oke Anandika Lestari; Lucky Hartanti (Universitas Trilogi, 2026)
Tempe tapioca chips are chips made from soybean or other raw materials and mixed with yeast and tapioca, then fermented to a solid form like tempeh, and fried before consumption. The legume group (soya) is high in the amino acid lysine, but low in the amino acid methionine, as opposed to cereals. Therefore, the combination of soya with corn in the manufacture of tempe tapioca chips can potentially complement the nutrition of the final product. The objective of the study was to obtain the addition of tapioca that produces the best physicochemical and sensory characteristics of tempe tapioca chips. This research used Randomised Group Design (RAK) with 4 treatment levels, namely 25g (20%), 50g (33%), 75g (43%), and 100g (50%). Based on the results of the study, the best tempeh tapioca chips were added with 50g (33%) tapioca with the results of moisture content of 2.69%, acid insoluble ash content of 0.03%, protein content of 14.72%, crispness of 45.71% and had descriptive sensory characteristics of yellow colour, mild flavour, mild tempeh taste, crisp texture and preference level.